Change my body, change my mind: the effects of illusory ownership of an outgroup hand on implicit attitudes toward that outgroup - Farmer, Harry; Maister, Lara; Tsakiris, Manos (Frontiers in Psychology, 2014)
The effect of multisensory-induced changes on body-ownership and self-awareness using bodily illusions has been well established. More recently, experimental manipulation of bodily illusions have been combined with social cognition tasks to investigate whether changes in body-ownership can in turn change the way we perceive others. For example, experiencing ownership over a dark-skin rubber hand reduces implicit bias against dark-skin groups. Several studies have also shown that processing of skin colour and facial features play an important role in judgements of racial typicality and racial categorization independently and in an additive manner. The present study aimed at examining whether using multisensory stimulation to induce feelings of body ownership over a dark-skin rubber hand would lead to an increase in positive attitudes towards black faces. We here show, that the induced ownership of a body-part of different skin colour affected the participants’ implicit attitudes when processing facial features, in addition to the processing of skin colour as shown previously. Furthermore, when the levels of pre-existing attitudes towards black people were taken into account, the effect of the rubber hand illusion on the post-stimulation implicit attitudes was only significant for those participants who had a negative initial attitude towards black people, with no significant effects found for those who had positive initial attitudes towards black people. Taken together, our findings corroborate the hypothesis that the representation of the self and its relation to others, as given to us by body-related multisensory processing, is critical in maintaining but also in changing social attitudes.